A naked eye colorimetric sensor for alcohol vapor discrimination and amplified spontaneous emission (ASE) from a highly fluorescent excited-state intramolecular proton transfer (ESIPT) molecule. Issue 29 (4th July 2016) - Chen, Ling; Yin, Shao-Yun; Pan, Mei; Wu, Kai; Wang, Hai-Ping; Fan, Ya-Nan; Su, Cheng-Yong
Abstract : The special four-energy level of ESIPT molecule H2 hpi2cf results in both naked-eye colorimetric discrimination of common alcohols and ASE photophysical properties. Abstract : A highly fluorescent HPI-based excited-state intramolecular proton transfer (ESIPT) molecule is designed and adopted as a naked-eye colorimetric sensor to distinguish methanol, ethanol and isopropanol vapors. Amplified spontaneous emission was also observed for the C1-form single crystal of the molecule attributed to its intrinsic four-level energy states.